CFD2CFD: How computational fluid Dynamics can be a means towards sustainable conscious field dynamics - M Hilman Gumelar Syafei; Illa Rizianiza; Ahmad Indra Siswantara; Angga Septiyana; Adi Syuriadi; Muhammad Agung Santoso; Ahmad Syihan Auzani (BKS-TM Indonesia, 2025)
The role of Computational Fluid Dynamics (CFD) across diverse applications has been significantly reinforced by rapid advancements in numerical computation, artificial intelligence, and high-performance computing. Nevertheless, prevailing applications of CFD predominantly operate as simulation tools and technical solutions, often neglecting dimensions of awareness, intentionality, and ethical considerations. This study introduces the CFD2CFD paradigm (Computable Field Dynamics to Conscious Field Dynamics), which is conceptualized within the DAI5 framework—comprising Deep Awareness of I, Intention, Initial Thinking, Idealization, and Instruction Set. In this paradigm, Computable Field Dynamics is defined as the material field that can be mathematically represented and numerically resolved, while Conscious Field Dynamics denotes the immaterial field of awareness. To demonstrate this approach, case studies are conducted on representative material fluid phenomena, namely pipe flow, airfoil aerodynamics, and biomass pyrolysis. The integration of Computable Field Dynamics and Conscious Field Dynamics through the DAI5 framework establishes a novel methodological pathway. The contribution of the CFD2CFD paradigm lies in its provision of a computational approach that extends beyond scientific accuracy to encompass sustainability considerations. More importantly, this paradigm is formulated as an epistemic bridge uniting material and immaterial fields, thereby offering a framework for methods that are simultaneously rigorous in scientific validity and oriented toward sustainability.